2017
DOI: 10.21077/ijf.2017.64.2.62418-08
|View full text |Cite
|
Sign up to set email alerts
|

Use of phytase at graded levels for improving nutrient digestibility, growth and hematology of Catla catla fingerlings fed Moringa oleifera seed meal (MOSM) based diet

Abstract: Present research work was conducted to evaluate the effect of phytase supplementation on nutrient digestibility, growth performance and hematological indices of Catla catla (Hamilton, 1822) fingerlings fed Moringa oleifera seed meal (MOSM) based diet. Existence of phytate in plant byproducts decreases the bioavailability of nutrients to fish, resulting in low nutrients availability, poor fish growth and hematological indices in fish body. Moringa byproducts such as M. oleifera seed meal (MOSM) was used as test… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 42 publications
(53 reference statements)
3
6
0
Order By: Relevance
“…ADC of GE also increased to its maximum (71%) at 950 FTU kg −1 amount of PHY, followed by digestibility co-efficient (69%) at 800 FTU kg −1 . Hussain et al (2017) reported maximum GE (74%) at 900 FTU kg −1 in C. catla , that is very close to our results. While, lowest value of GE (53%) was found at diet with 0 FTU kg −1 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…ADC of GE also increased to its maximum (71%) at 950 FTU kg −1 amount of PHY, followed by digestibility co-efficient (69%) at 800 FTU kg −1 . Hussain et al (2017) reported maximum GE (74%) at 900 FTU kg −1 in C. catla , that is very close to our results. While, lowest value of GE (53%) was found at diet with 0 FTU kg −1 .…”
Section: Discussionsupporting
confidence: 92%
“…Maximum growth performance in terms of WG (19 g), FCR (1.10) and SGR (1.67) was estimated in C. carpio at 950 FTU kg −1 of PHY, followed by 800 FTU kg −1 . Like above mentioned results, Hussain et al, 2017 , Shahzad et al, 2018b found highest growth performance in C. catla when fed on a PHY supplemented (900 FTU kg −1 ) moringa by-product based diet in comparison of control and other PHY supplemented diets. Maas et al (2019) observed improved growth performance in Nile tilapia at 1000 FTU kg −1 supplemented in sunflower meal based diet.…”
Section: Discussionmentioning
confidence: 51%
“…The involvement of phytase in increasing protein digestibility is not direct, in fact, it is an outcome of phytase action on the digestibility of amino acid 48 . Phytase helps in retaining more nutrients inside the fish body 32,70,71,131 . Increased digestibility of minerals such as Fe, Mg, Ca, P, K, Zn, Cu, Na, Al, Mn, Sr, Cr and Pb has been observed in O .…”
Section: Nutrients Digestibilitymentioning
confidence: 99%
“…48 Phytase helps in retaining more nutrients inside the fish body. 32,70,71,131 Protein as well as P digestibility was higher when dietary protein and phytase were added to the diet of O. mykiss 60 and C. gariepinus. 119 Although, the apparent digestibility of protein, ash, and P was more in P. maxima, the absorption of minerals remained unaffected.…”
Section: Nutrients Digestibilitymentioning
confidence: 99%
“…Due to this potential, the utilization of phytase is currently being extensively assessed [15]. Various studies have been conducted on phytase supplementation in plant-based diets, which have shown enhanced growth performance and nutrient utilization in fish species [16][17][18][19]. However, no study on RPC-based diets has been reported.…”
Section: Introductionmentioning
confidence: 99%